2016
DOI: 10.1080/09540253.2016.1237619
|View full text |Cite
|
Sign up to set email alerts
|

Snow White in Hellenic primary classrooms: children’s responses to non-traditional gender discourses

Abstract: This paper sets out to investigate how children make sense of and negotiate nontraditional gender discourses promoted through the feminist version of the fairytale of Snow White. The research was based on work with 120 pupils aged 9-11 years old in two Athenian primary schools. The data was collected through semi-structured group interviews. The findings suggested that schoolchildren gave conflicting accounts in relation to gender discourses and identities. There is a strong indication that girls of this age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 29 publications
1
22
0
9
Order By: Relevance
“…Post-structuralist theory focuses on the different gender discourses available in a given social context and on the way in which children learn gender in their daily interactions. In this context, it is understood that they can practice diverse or even contradictory discourses of gender, resisting, at times, the discourses of dominant masculinity and femininity (Kostas, 2018;Rodríguez & Peña, 2005). Post-structuralist theory suggests that children do not act as passive readers, reproducing dominant gender discourses, but, in their interaction with literature, they explore new gender discourses (Änggård, 2005;Bartholomaeus, 2016;Dallacqua, 2019;Davies, 1989;Jackson, 2007).…”
Section: Post-structuralist Theory: Boys and Girls As Active Readersmentioning
confidence: 99%
See 4 more Smart Citations
“…Post-structuralist theory focuses on the different gender discourses available in a given social context and on the way in which children learn gender in their daily interactions. In this context, it is understood that they can practice diverse or even contradictory discourses of gender, resisting, at times, the discourses of dominant masculinity and femininity (Kostas, 2018;Rodríguez & Peña, 2005). Post-structuralist theory suggests that children do not act as passive readers, reproducing dominant gender discourses, but, in their interaction with literature, they explore new gender discourses (Änggård, 2005;Bartholomaeus, 2016;Dallacqua, 2019;Davies, 1989;Jackson, 2007).…”
Section: Post-structuralist Theory: Boys and Girls As Active Readersmentioning
confidence: 99%
“…Following the study of Davies (1989), recent research has shown that gender dualisms exert an important influence on the interpretations that children make of feminist stories (Baker-Sperry, 2007;Bartholomaeus, 2016;Kostas, 2018). Kostas (2018), for example, held reading groups with children to discuss a feminist version of Snow White's story and found that they reproduced the binary construction of gender, identifying weakness with femininity. They understood that Snow White, in her position as a mine worker, had sacrificed her femininity to be like a man.…”
Section: Previous Research On the Understanding Of Feminist Storiesmentioning
confidence: 99%
See 3 more Smart Citations